A precarização do trabalho do assistente social no contexto da disseminação das Tecnologias de Informação e Comunicação (TICs) - Sobrinho, Alfredo Pantoja Azevedo (Brasil, 2025)
The current scenario of global capitalism is configured for commodification, flexibilization and precariousness of work, which shape the structure of the societal scale. In this dimension, the social worker workforce is integrated into the context of new technologies and their actions in confronting the manifestations of the “Social Question”. Given this premise, this study has as its main focus the understanding of the precariousness of the work of the social worker in the context of the dissemination of ICTs. To achieve success, the methodological path had as an approach qualitative research, using bibliographic research as a method of procedure, bringing together the main scientific productions that address the aforementioned theme. The results demonstrate that ICTs have spread across all professional categories, among them Social Work. These technologies are considered important tools for consolidating the accumulation of capital and its mechanisms of exploitation and control of the workforce. With the advent of information and the new demands of the labor market, ICTs have contributed to the precariousness of the work of the social worker and to the degradation of social and labor rights. Thus, it is concluded that precariousness permeates the relationships and working conditions of social workers, a reality that is determined by capitalism and the hegemony of bourgeois society. Keywords: Flexibility. Precariousness. Work. Social Worker. ICTs.